Penurunan COD, BOD DAN TSS Pada Limbah Cair Industri Tahu Melalui Sistem Multy Soil Layering (MSL) Menggunakan Arang Karbon Ampas Tebu - Novela, Dessy (RC-INSTITUT, 2019)
Tofu industry is one of the industries which causing pollution on the environment especially  water  environment.  The  amount  of  wastewater-dumped  and  the  content  of organic substances could damage the water ecosystem. Multi Soil Layering (MSL) as one of alternative method is used in order to remove the tofu industrial wastewater pollution. MSL  is  a  method  of  wastewater  treatment  that  enhances  the  function  of  soils  to  purify wastewater. The  research  aimed  to  determine  optimum  loading  rate  and  efficiency  of  MSL system to remove TSS, BOD and COD. This research was carried out in February, 2019. The results revealed efficiency of MSL  system  to  remove  TSS,  BOD  and  COD   were  86,86% ; 78,05% ; and 89,75 % respectively.